Инклузивно образование или инклузивно посебно образование - Димитрова Радојичиќ, Даниела; Чичевска Јованова, Наташа (Faculty of Philosophy, Skopje, 2018)
Inclusive education and special education are based on different philosophies and provide alternative views of education for children with disabilities. They are increasingly regarded as diametrically opposed in their approaches. The aim of this article is to present a new model of Inclusive Special Education, presented by Horbny (2014). This model synthesises the philosophy and values of inclusive education with the practices and technology of special education. In this theory aspects of both approaches are combined to form inclusive special education. The goal of inclusive special education is to ensure that all children are effectively educated in either special or mainstream facilities from early childhood through high school education, in order to achieve their maximum possible inclusion.
Inclusive education or Inclusive special education
Keywords: students with disability, inclusive education, special education, inclusive special education